Tocolytic Effect of White Pepper (Piper nigrum Linn.) on Isolated Rat Uterine Contraction in vitro - Sawangjaroen, Kitja; Sarnkhaeveerakul, Pidyada (Trends in Sciences, 2023)
Piper nigrum Linn. (Pepper) is a very well-known spice used for different purposes such as human dietaries, medicine and preservative. In Thai traditional medicine, white pepper is a component of herbal formulas used to treat many disorders including symptoms of dysmenorrhea. It is of interest to investigate the effect of methanolic extract of white pepper (MEWP) on the isolated rat uterus contractions induced by various uterine stimulants and the possible mechanism(s) involved. Strips of uterus were prepared from estrogen-primed female Wistar rats, fixed in the organ bath filled with an appropriate physiological solution with carbogen bubbled continuously at 37 °C. The measurement of isometric tension was then performed using force transducer attached to a polygraph. MEWP was tested its effect on the uterine contraction and found the inhibitory effects on the contraction induced by oxytocin, PGF2α and depolarizing solution. TEA inhibited the uterine relaxing effect of MEWP while glibenclamide had no effects when the uterus was induced to contract with oxytocin. Propranolol abolished the uterine relaxing effect of isoproterenol while it had no effects on the relaxing effect of MEWP. The results suggested that MEWP is likely to be a general uterine relaxant. The effects may be due to the interference on Ca2+ influx into the uterine muscle cells which may involve the opening of KCa channel. The effect was unlikely to occur via the KATP-channel and may not involve the interaction of MEWP on b-adrenergic receptor on the uterine muscle cells. HIGHLIGHTS Methanolic extract of white pepper (MEWP) is likely to be a general uterine relaxant. The uterine relaxing effect of MEWP may involve an inhibition of a rise in intracellular Ca2+ from both Ca2+ influx via plasma membrane of the uterine smooth muscle cell and probably Ca2+ release from internal storage. The effect of MEWP may be mediated mainly through a reduction in Ca2+ influx, possibly through voltage dependent Ca2+ The effect of MEWP may involve with the opening of KCa channel, which may arise from direct action of MEWP on the calcium channel or be a consequence of an increase in [Ca2+]i. The uterine relaxing effect of MEWP is unlikely to be mediated by an activation of β2 –adrenergic receptor. GRAPHICAL ABSTRACT